2022
DOI: 10.3389/fonc.2022.1018248
|View full text |Cite
|
Sign up to set email alerts
|

The role of the endoscopic grading of gastric intestinal metaplasia in assessing gastric cancer risk: A systematic review and meta-analysis

Abstract: Background and aimPatients with gastric intestinal metaplasia (IM) are at increased risk of gastric cancer (GC). The endoscopic grading of gastric intestinal metaplasia (EGGIM) with high-definition endoscopes has shown the potential to facilitate GC risk stratification. However, a comprehensive review and meta-analysis of published articles are lacking. We conducted a meta-analysis to access the value of EGGIM in the assessment of histological IM.MaterialsStudies were selected from PubMed, Medline, Embase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Higher stage (OLGA/OLGIM III/IV) is associated with a higher risk of gastric cancer as compared with lower-stage atrophy/IM, as demonstrated in a meta-analysis published in 2018, where the odds ratios for gastric cancer for OLGA and OLGIM, respectively, were 2.64 (95% CI: 1.84-3.79) and 3.99 (95% CI: 3.05, 5.21). Importantly, EGGIM ≥5 has high concordance with OLGIM III/IV with an AUC of 0.97, reinforcing the role of endoscopic evaluation as a means of risk assessment [83]. However, OLGIM stage I/II still carries an increased risk of cancer.…”
Section: Histologic Featuresmentioning
confidence: 82%
See 1 more Smart Citation
“…Higher stage (OLGA/OLGIM III/IV) is associated with a higher risk of gastric cancer as compared with lower-stage atrophy/IM, as demonstrated in a meta-analysis published in 2018, where the odds ratios for gastric cancer for OLGA and OLGIM, respectively, were 2.64 (95% CI: 1.84-3.79) and 3.99 (95% CI: 3.05, 5.21). Importantly, EGGIM ≥5 has high concordance with OLGIM III/IV with an AUC of 0.97, reinforcing the role of endoscopic evaluation as a means of risk assessment [83]. However, OLGIM stage I/II still carries an increased risk of cancer.…”
Section: Histologic Featuresmentioning
confidence: 82%
“…For each region, extent is scored as 0 (no IM), 1 (≤30% IM) or 2 (>30% IM), giving a maximum score of 10. An EGGIM score ≥5 is considered higher risk, and a small 2022 meta-analysis of three studies demonstrated an odds ratio of 7.46 (95% CI 3.41 to 16.31) for early gastric neoplasia when compared with EGGIM 0-4 [83].…”
Section: Endoscopic Featuresmentioning
confidence: 99%